2004
DOI: 10.1177/1468794104044432
|View full text |Cite
|
Sign up to set email alerts
|

Where Qualitative Research Meets Demography: Interdisciplinary Explorations of Conceptions of Fatherhood in an Extremely Low Fertility Context

Abstract: Recent calls to include psychological theories of decisionmaking and intention-formation in research on family formation coincide with calls for improving research on male fertility and fatherhood. In this article we address these notions and present findings from in-depth interviews with 30-year-old childless men from Eastern Germany on their desire to become parents. The context for this research is the societal situation of contemporary Eastern Germany, where birth rates have faced a historical low - the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Nascent fathers revealed somewhat vague plans and expectations concerning approaching fatherhood. Similar findings were advanced by Von Der Lippe and Fuhrer (2004), who concluded that many 30-year-old childless East German men had difficulties both anticipating fatherhood and forming detailed impressions before the event. This approach was evident with respect to the sample of fathers-to-be described in this study.…”
Section: Expectations Of Nascent Fatherssupporting
confidence: 72%
“…Nascent fathers revealed somewhat vague plans and expectations concerning approaching fatherhood. Similar findings were advanced by Von Der Lippe and Fuhrer (2004), who concluded that many 30-year-old childless East German men had difficulties both anticipating fatherhood and forming detailed impressions before the event. This approach was evident with respect to the sample of fathers-to-be described in this study.…”
Section: Expectations Of Nascent Fatherssupporting
confidence: 72%
“…Studies on the decision to have children usually only included either women (Den Bandt 1982;Gerson 1985;Van Luijn 1996;Wijsen 2002;Bernardi 2003;Sevón 2005) or, to a much lesser extent, men (Jacobs 1995;Von der Lippe and Fuhrer 2004;Knijn, Ostner, and Schmitt 2006). We included both partners in this study by having in-depth interviews with couples.…”
Section: Introductionmentioning
confidence: 99%